Patterns of knowledge used by nurses in caring for the patient in the first psychotic outbreak - Andressa de Oliveira; Ana Paula Rigon Francischetti Garcia; Vanessa Pellegrino Toledo (Escola Anna Nery, 2017)
Abstract Objective: To know how the nurse provides care in the first psychotic outbreak of patients, and to identify the Barbara Carper patterns of knowing used for this action. Methods: A qualitative study using a phenomenological approach was performed in four Psychosocial Care Centers and in a psychiatric ward of a university hospital. Data collection was carried out with ten nurses participating in semi-structured interviews using the following guiding question: "Tell me your experience in caring for a patient in their first psychotic outbreak". Results: Carper's fundamental ways of knowing (empirical, aesthetic, ethical and personal) were identified in the caring of the patient in their first psychotic outbreak. Conclusion and Implications: A fragmented practice is implied when patterns of knowledge are taken in isolation. This reflects on specific actions of nursing work, such as the nursing practice and its stages.